Pneumocystis jiroveci pneumonia prophylaxis is a challenge in granulomatosis with polyangiitis patients treated with rituximab. - Besada,Emilio (PeerJ PrePrints, 2013)
All strategies to prevent Pneumocystis jiroveci pneumonia (PCP) during rituximab treatment have their rationale in patients with granulomatosis with polyangiitis (GPA) and to some extent in patients with other autoimmune diseases (AID). Risk factors of PCP and severe infections are very similar in GPA patients. The decision of PCP prophylaxis should not be limited at RTX initiation and during RTX treatment, but should be reassessed continuously in all GPA patients. Since PCP increases the mortality risk in GPA (and AID) patients, the treating physician should always consider PCP as a possible diagnosis in patients treated with RTX - receiving or not PCP prophylaxis.
Keywords: rituximab; granulomatosis with polyangiitis; anca-associated vasculitis; pneumocystis jiroveci pneumonia; pneumonia; B cell depeltion; CD4 cell count; infection; prophylaxis; autoimmune disease